2010
DOI: 10.1089/env.2010.0014
|View full text |Cite
|
Sign up to set email alerts
|

Governance Structures and the Lack of Basic Amenities: Can Community Engagement Be Effectively Used to Address Environmental Injustice in Underserved Black Communities?

Abstract: Many communities impacted by environmental injustice, including the disproportionate burden of unhealthy land uses and environmental hazards and lack of access to health-promoting infrastructure, can trace these disparities to inequities in planning, zoning, and community development. These inequities and infrastructure disparities occur in many places because of the way that governance structures, particularly municipal police powers, are applied differentially and how in some cases these legal structures dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…These conditions include selective enforcement of drinking water regulations, 15 noncompliance with federal standards, 16,17 inequities in access to funding, 18 and (the absence of) a community's political power in accessing a safe water supply. 19 Research has also shown that cost of service extension and low ability to pay drive inadequate service provision 2 ; that municipalities provide or deny access to basic services by determining which areas to annex or exclude from their city boundaries 4,10,20 ;…”
Section: 14mentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions include selective enforcement of drinking water regulations, 15 noncompliance with federal standards, 16,17 inequities in access to funding, 18 and (the absence of) a community's political power in accessing a safe water supply. 19 Research has also shown that cost of service extension and low ability to pay drive inadequate service provision 2 ; that municipalities provide or deny access to basic services by determining which areas to annex or exclude from their city boundaries 4,10,20 ;…”
Section: 14mentioning
confidence: 99%
“…Wilson et al have shown that disparities in "basic amenities" drive adverse health outcomes, especially in conjunction with poorly enforced health laws and building codes. 4,10 VanDerslice's infrastructure-oriented framework posits that the extent to which any aspect of water infrastructure-natural, built, or managerialdiffers by racial or income disparities drives disparities in water quality, reliability, and cost. 11 The literature also notes that small water systems are vulnerable to inadequate regulatory protection, 12 and to uneven monitoring and reporting.…”
mentioning
confidence: 99%
“…In his presentation, he described approaches WERA used to seek basic amenities such as first-time installation of publicly regulated sewer and water infrastructure using the community-owned and managed research (COMR) approach [19][20][21][22][23] and collaborative problem-solving model (CPSM). [19][20][21][22][23] He also discussed the use of administrative complaints and Title VI to address environmental justice and health problems.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the literature examining institutional practices relevant to walkability, there is a body of work of looking at grassroots engagement (Bergman et al 2002, DeFrancesco et al 2003, Hardwood 2003, Newman et al 2008, Dobson and Gilroy 2009, Hamamoto et al 2009, Hooker et al 2009, Raja et al 2009, Williams et al 2010, Wilson et al 2010. This research takes a "bottom-up" perspective and examines the role of citizens and neighbourhood groups in creating more walkable environments.…”
Section: Present State Of Knowledgementioning
confidence: 99%
“…We argue that understanding the dayto-day democratic processes that allow pedestrian concerns at the neighbourhood level to move up to policy or action at the municipal level will be critical to creating walkable places in the future. The literature on environmental justice has documented a number of cases in which governance structures and municipal policies have unfairly disadvantaged lower income and African American communities, resulting in disproportionate environmental exposures and adverse health outcomes (Bullard 1996, Rhodes 2003, Wilson et al 2010. There is evidence that these disadvantages also extend to lower quality walking conditions (Estabrooks et al 2003, Greenberg and Renne 2005, Aytur et al 2008.…”
Section: Introductionmentioning
confidence: 99%